PS6:110 Motor and cognitive fatigue in sle is associated with mood and health-related quality of life (hrqol) in patients with sle: results from the patient reported outcomes in lupus (pro-lupus) study. (21st March 2018) - Bland, A; Hunziker, S; Barraclough, M; Kane, K; Cervera, R; Dörner, T; Doria, A; Pouchot, J; Stoll, T; Penner, I-K; Bruce, IN
Abstract : Background: Fatigue is a commonly reported problem in systemic lupus erythematosus (SLE) but the cause and impact of this symptom are not fully understood. Clinical, physical and psychosocial aspects may affect fatigue as well as cognitive performance. Of note, the influence of disease status and inflammatory disease activity on fatigue in SLE is poorly understood. We aimed to better understand these associations by studying changes in fatigue over time. Methods: 100 SLE patients, all with lupus nephritis, were recruited across 5 European countries. Participants completed assessments examining; fatigue (FSMC: Fatigue Scale for Motor and Cognitive functions), disease activity (SLEDAI, tender joints score), SLICC damage index, cognition (SPRT: Spatial Recall Test, SDMT: Symbol Digits Modalities Test, PASAT: Paced Auditory Serial Addition Test, SRT: Selective Reminding Test, WLG: Word List Generation), pain (pain mannequin), depression (CES-D: Centre for Epidemiological Studies-Depression Scale), steroid dose and HRQoL (SF-36 v2, LupusQoL), at baseline and at follow-up, 3–4 months later. Correlations of score changes between baseline and follow-up were calculated using SPSS 22 and any significant results (p<0.01) are reported below. Results: All participants met 1997 revised ACR criteria for SLE and had biopsy-proven lupus nephritis (ISN grades II-V). The mean (SD) SLEDAI score was 4.67 (5.05) at baseline and 4.37 (5.55) at follow-up. Cognitive scores were significantly different at baseline compared to follow-up, where all scores improved. When examining the correlations between changes in score from baseline to follow-up, there were significant associations between changes in fatigue (motor and cognitive) scores with mood, the physical subscale of the SF-36 and a number of domains of the LupusQOL including pain and burden to others (Table 1). No significant correlations were found between changes in fatigue and disease activity, damage, steroid dose or cognitive measures. Conclusions: In SLE patients the major associations of motor and cognitive fatigue are with mood, pain and poorer HRQoL. We found no significant correlations with disease activity, damage or steroid dose. Self-rated QoL and depression may more directly impact fatigue than disease activity and these psychosocial aspects need to be addressed to help manage fatigue more effectively in SLE.